2011
DOI: 10.1103/physreva.83.032315
|View full text |Cite
|
Sign up to set email alerts
|

Precision requirements for spin-echo-based quantum memories

Abstract: Spin-echo techniques are essential for achieving long coherence times in solid-state quantum memories for light because of inhomogeneous broadening of the spin transitions. It has been suggested that unrealistic levels of precision for the radio-frequency control pulses would be necessary for successful decoherence control at the quantum level. Here we study the effects of pulse imperfections in detail, using both a semiclassical and a fully quantum-mechanical approach. Our results show that high efficiencies … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
1
12
1
Order By: Relevance
“…dynamical decoupling). This was studied in [69] which showed that this within the reach of realistic levels of precision.…”
Section: Rare-earth Doped Solidsmentioning
confidence: 99%
“…dynamical decoupling). This was studied in [69] which showed that this within the reach of realistic levels of precision.…”
Section: Rare-earth Doped Solidsmentioning
confidence: 99%
“…The influence of nonideal π pulses on the quantum efficiency and noise in free-space optical quantum memories has been discussed in [40]. It has been shown that n equalled pulses with pulse area π ± δ reduces the quantum efficiency due to the factor ∼(1 − n 2 N s δ 2 ).…”
Section: Time-delay Retrieval and Dynamical Decouplingmentioning
confidence: 99%
“…The challenge lies in avoiding to populate the |s state with too many atoms, which would lead to spontaneous emission noise in the output when reading out the single spin excitation. At first this might appear to be almost impossible for a single excitation in |s [124], but it was shown later that the strong collective emission into a particular spatial mode of the stored single excitation provides a very effective spatial filtering of the spontaneous emission noise [125]. The spin-echo technique must be very efficient, however, to avoid this noise, and it remains to be seen if the storage fidelity of a single photon can be high enough when applying spin echo techniques.…”
Section: Prospects For Spin-wave Storage With Quantum Lightmentioning
confidence: 99%